2021
DOI: 10.1049/sil2.12025
|View full text |Cite
|
Sign up to set email alerts
|

Recursive joint Cramér‐Rao lower bound for parametric systems with two‐adjacent‐states dependent measurements

Abstract: Joint Cramér-Rao lower bound ( JCRLB) is very useful for the performance evaluation of joint state and parameter estimation ( JSPE) of non-linear systems, in which the current measurement only depends on the current state. However, in reality, the non-linear systems with two-adjacent-states dependent (TASD) measurements, that is, the current measurement is dependent on the current state as well as the most recent previous state, are also common. First, the recursive JCRLB for the general form of such non-linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…To initialize the recursion for FIMs of prediction and smoothing, the recursion of the FIM J k|k for filtering is required. This can be obtained from Corollary 3 of [51], as shown in the following lemma.…”
Section: Bcrlbs For General Tasd Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…To initialize the recursion for FIMs of prediction and smoothing, the recursion of the FIM J k|k for filtering is required. This can be obtained from Corollary 3 of [51], as shown in the following lemma.…”
Section: Bcrlbs For General Tasd Systemsmentioning
confidence: 99%
“…In practice, the TASD systems sometimes may incorporate some unknown nonrandom parameters. For the performance evaluation of joint state and parameter estimation for nonlinear parametric TASD systems, a recursive joint CRLB (JCRLB) was studied in [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determinant of the Fisher Information Matrix (FIM) is used to represent the observability measurement of the system, thereby providing a usable optimization index for the detection system [ 10 , 11 , 12 ]. Further research found that CRLB is equal to the inverse of FIM [ 13 , 14 ], which unified the positioning accuracy index and the observability index.…”
Section: Introductionmentioning
confidence: 99%